Flipped classroom as a mathematics learning space for part-time students - Justino, Júlia (2021)
This paper presents a study developed in the implementation of flipped learning approach in a Mathematics course unit of an evening higher education degree, mostly attended by student workers. The pedagogical model based on flipped learning combined with active learning techniques, which complements the acquisition of mathematical scientific skills with autonomy, teamwork, mutual help and critical thinking, is described. Outcomes of the implementation of this pedagogical model are also presented and discussed.